The didactic resources and their incidence in the development of skills in the students of Julio Ernesto Celi Roman high school of Jimbura parish. Academic period 2007-2008 - Jiménez Jiménez, María Germania (2008)
The use of didactic resources in the teaching has been a great tool of supporting, mainly in a foreign language; they help to get certain objectives that want to get during the class. The main objective of this research is to describe how the didactic resources incide in the development of skills in the students of “Julio E. Celi R.” , of Jimbura Parish in the academic period 2007-2008, to compile the information were used the direct observation and survey techniques, applied to teachers and students respectively. For processing the information the inductive – deductive, analytical methods were used; and, the descriptive method to elaborate the report. Among the main results of the researching work we found: the lack of didactic resources and the application of them, the use of traditional material, the few interest in students and the limitation of technological and economic resources. Referring to qualification of teachers, they receive training from CRADLE Project, about didactic resources elaboration, and other topics related to the teaching learning process.